Interreligious Friendship after Nostra Aetate - Fredericks, J.; Tiemeier, T.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
Interreligious Friendships after Nostra Aetate explores the ways in which personal relationships are essential for theology. Catholic theologians tell the personal stories of their interreligious friendships and explore the significance of their friendships for their own life and work.
Keywords: Religion and sociology; Religions; Catholic Church; Religion and Society; Sociology of Religion; Comparative Religion; Social Aspects of Religion; Catholicism